Approaches to cognition through text and discourse - Virtanen, Tuija (Trends in linguistics. Studies and monographs, 2004)
This book explores the overlapping area of study that discourse linguists and cognitive linguists are interested in. It procedes from considerations of information structuring, coherence and foregrounding to those of negotiation of meaning in situational and cultural contexts. The cognitive issues brought to the fore range from assumptions that we make about the interlocuters' memory constraints, the relative salience that we give to and recognize in elements of discourse, prototypicality and the figure-ground distinction reflected in language use, locative concerns, iconicity, negotiation bet.